Da’wah Model Through Facebook Social Media Platform - Abd Rasyid Masri; Mahmuddin Mahmuddin; Hamka Mahmud (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2022)
This study aims to map the pattern and model of da'wah through social media. Facebook as a medium of da'wah in the digital era. Specifically, the research is directed at analyzing the packaging process, delivery and public response in receiving the message of KH's M Arif Marzuki Hasan da’wah through the Facebook page of the Darul Istiqamah Islamic Boarding School Maccopa, South Sulawesi. This research is qualitative research using a historical approach and da'wah. The data collection techniques were carried out through observation, interviews, and literature. The results show that the form and model of da'wah delivered through the social media platform Facebook is one of the innovative ways of transmitting and disseminating da'wah messages. The public's response as the object of da'wah views that the convergence of da'wah media on the Facebook platform is seen as providing benefits according to the category of da'wah messages in terms of interpretation of the Qur'an, morality, aqidah and shari'ah. The implication of the research shows that there is a need to develop a da'wah model through a more varied pattern of packaging da'wah content. In addition, with social media platforms, da'wah is an alternative to capturing opportunities for digital da'wah activities.